Aberrant Origin of Vertebral Artery and its Clinical Implications - Yuan,Shi-Min (2016)
Abstract Aberrant origin of vertebral artery is rare. The anatomical features and clinical significance of this lesion remain to be clarified. A comprehensive collection of the pertinent literature resulted in a cohort of 1286 cases involving 955 patients and 331 cadavers. There were more left than right and more unilateral than bilateral aberrant vertebral arteries. Patients with aberrant origin of vertebral artery were often asymptomatic and in only 5.5% of the patients their symptoms were probably related to the aberrant origin of vertebral artery. The acquired cardiovascular lesions were present in 9.5% of the patients, 20.9% of which were vertebral artery-associated lesions. Eight (0.8%) patients had a vertebral artery dissection. Logistic regression analysis showed significant regressions between bovine trunk and left vertebral artery (P=0.000), between the dual origins of vertebral artery and cerebral infarct/thrombus (P=0.041), between associated alternative congenital vascular variants and cervical/aortic dissection/atherosclerosis (P=0.008). Multiple logistic regression demonstrated that side of the aberrant origin of vertebral artery (left vertebral artery) (P=0.014), arch branch pattern (direct arch origin) (P=0.019), presence of the common trunk (P=0.019), associated acquired vascular disorder (P=0.034) and the patients who warranted management (P=0.000) were significant risk predictors for neurological sequelea. The patients with neurological symptoms and those for neck and chest operations/ interventions should be carefully screened for the possibility of an aberrant origin of vertebral artery. The results from the cadaver metrology study are very helpful in the design of the aortic stent. The arch branch pattern has to be taken into consideration before any maneuver in the local region so as to avoid unexpected events in relation to aberrant vertebral artery.